STUDY OF HYDROGEOLOGICAL FUNCTIONING OF COMPLEX TERMINAL (CT) AQUIFER, USING HYDROGEOCHEMICAL AND ISOTOPIC TOOLS: CASE STUDY OF OUED SOUF REGION (SOUTHEAST OF ALGERIA) - Ali NESRAT; Serhane BRAHMI; Chemseddine FEHDI; Tarek DJEDID; Salim KHACHANA (Food and Environment Safety, 2023)
The largest confined aquifers hydraulically continuous from the Algeria Atlas Mountains as a recharge area to the Tunisian Chotts were discharge area. Is being largely used in the valley of Oued Souf, southeastern of Algeria and part of the northeastern Sahara, composed with sedimentary series ranging from the lower Cretaceous to the Quaternary. These formations have favored several aquifer layers with variable hydrodynamic behavior depending on their facies. The high expansion of the agricultural field needs irrigation from groundwater aquifers in this area. The overexploitation of the shallow aquifer causes severe deterioration of groundwater quality and soil suffusion at arid areas. The high salinity (electrical conductivity exceeds 3600 mS.cm-¹) coupled with groundwater level decline pose serious problems for current irrigation and domestic water supplies. Although, the multi-layers of complex terminal (CT) and continental intercalary (CI) aquifers is used to approve the water supplies. In aim to corroborate the hydrochemical process, and to investigate the water potentialities and mineralization of CT and CI groundwater aquifers, chemical tools namely major elements and trace elements are studied. The isotopic (δ 18O, δ 2H) hydrogeochemical study helps to identify and classify this deep underground water aquifers relationship. The samples isotopic signal shown a current recharge of the CT, according to the regional rainfall signal.